The construct validity of over-claming as a measure of egoistic enhancement - Tonković Grabovac, Maša (Array, 2011)
Over-claiming is the tendency to claim knowledge about nonexistent items. Findings of the previous research suggest it might serve as a measure of unconscious egoistic bias, one form of socially desirable responding. The aim of this study was to examine the convergent and divergent validity of over-claiming within Paulhus two-tiered model of socially desirable responding. Total of 382 participants filled-in the Over-claiming Questionnaire, together with Comprehensive Inventory of Desirable Responding and IPIP-300 personality inventory, under honesty instructions. Results indicate that over-claiming might represent a measure of egoistic bias, but still is not enough clear whether this bias is conscious or unconscious.